Neonatal Natural Killer Cell Function: Relevance to Antiviral Immune Defense - Yen-Chang Lee; Syh-Jae Lin (Clinical and Developmental Immunology)
Neonates are particularly susceptible to various pathogens compared to adults, which is attributed in part to their immature innate and adaptive immunity. Natural killer cells provide first-line innate immune reactions against virus-infected cells without prior sensitization. This review updates phenotypic and functional deficiencies of neonatal cells compared to their adult counterparts and their clinical implications.